QAULAN SADIDAN PRINCIPLES AND FACTUALITY IN PUBLIC BROADCASTING INSTITUTION NEWS - Rachmat Kriyantono (Profetik: Jurnal Komunikasi, 2019)
Abstract. This study aims to test the hypothesis that, as a public broadcasting institution that serves the public interest, non-commercial, and the majority of audiences are Muslim, the principle of qaulan sadidan has been widely adopted in TVRI news. Islam has provided a grand-theory for the study of communication and journalistic, namely qaulan sadidan. This principle was later recognized in the Western academic world as factuality, which is part of the news objectivity. By using the content analysis method on 146 news items from September 23, 2018 to March 29, 2019, this study found that the principle of qaulan sadidan has dominated the TVRI news although there are still news that do not yet contain elements of factuality. Many TVRI news articles are written containing 5W and 1H. This study also used interviews with senior journalist to confirm the data from the content analysis. The interviews found that management had not periodically socialized the relevance of Islamic values to journalistic practices, the element of the "when" was often not delivered in the news because of the editorial oversupply of news, not because of the lack of understanding on journalistic theory. This study offers some propositions that TVRI news includes factual and non-factual news, although it is dominated by factual news, experience as a journalist helps the adoption of qaulan sadidan values, and the completeness of the news is also determined by the news availability. This research is expected to contribute to the development of communication studies in an Islamic perspective.Abstrak. Penelitian ini bertujuan menguji hipotesis bahwa sebagai lembaga penyiaran public yang melayani kepentingan public, bersifat tidak komersial, dan mayoritas audience beragama Islam maka prinsip qaulan sadidan telah banyak diadopsi dalam berita TVRI. Islam telah memberikan grand-theory bagi kajian ilmu komunikasi dan jurnalistik, yakni qaulan sadidan. Prinsip ini yang kemudian dikenal di dunia akademik Barat sebagai faktualitas, yang merupakan bagian objektivitas berita. Dengan menggunakan metode analisis isi terhadap  146 berita selama 23 September 2018 hingga 29 Maret 2019, penelitian ini menemukan bahwa prinsip qaulan sadidan telah mendominasi berita TVRI meski masih terdapat berita yang belum mengandung unsur faktualitas. Berita TVRI juga banyak yang ditulis dengan mengandung 5H dan 1H. Penelitian ini juga menggunakan wawancara terhadap jurnalis senior untuk melakukan konfirmasi data hasil analisis isi. Hasil wawancara menemukan bahwa manajemen belum secara berkala mensosialisasikan keterkaitan nilai-nilai Islam dan praktek jurnalistik, unsur berita “when” sering tidak disampaikan dalam berita karena redaksi kelebihan persediaan berita, bukan karena ketidakpahaman jurnalis pada teori jurnalistik. Pada akhirnya, penelitian ini menawarkan proposisi bahwa berita TVRI mencakup berita yang factual dan yang tidak factual, meskipun didominasi berita yang factual; pengalaman sebagai jurnalis membantu adopsi nilai-nilai qaulan sadidan; dan kelengkapan berita juga ditentukan banyak tidaknya ketersediaan berita di ruang redaksi. Penelitian ini diharapkan berkontribusi untuk pengembangan kajian komunikasi dalam perspektif Islam.